(untitled) (Journal of Medical & Health Sciences Review, 2025)
The synthesis of vanadium carbon nitride (V/g-C₃N₄) composites has been explored for their potential as antimicrobial and antioxidant agents. These materials were evaluated against Escherichia coli and Staphylococcus aureus using a combination of disc diffusion, well diffusion, and biofilm inhibition assays. Antioxidant properties were assessed through DPPH free radical scavenging analysis. V/g-C₃N₄ composites demonstrated notable antimicrobial activity, exhibiting inhibition zones comparable to ciprofloxacin, the standard antibiotic. In disc and well diffusion assays, the composites significantly inhibited the growth of both bacterial strains, with Staphylococcus aureus exhibiting marginally higher sensitivity. Biofilm inhibition assays revealed effective suppression of bacterial adhesion and biofilm formation, achieving biofilm inhibition percentages of approximately 17% for E. coli and 22.6% for S. aureus. These results underscore the potential of V/g-C₃N₄ in curbing biofilm-associated infections. Antioxidant activity was quantitatively measured using the DPPH assay, with radical scavenging efficiency consistently exceeding 52%. This performance highlights the dual functionality of V/g-C₃N₄ composites as both antimicrobial and antioxidant agents. Comparatively, ciprofloxacin demonstrated superior antibacterial activity but lacked antioxidant properties, emphasizing the multifaceted advantage of V/g-C₃N₄ composites in biomedical applications. The shake-flask method further validated the biocompatibility and antimicrobial effectiveness of V/g-C₃N₄. This study indicates that vanadium carbon nitride composites hold promise as versatile agents in combating oxidative stress and bacterial infections, particularly in environments where biofilm formation exacerbates antimicrobial resistance. Future studies will focus on optimizing the composite synthesis and exploring its efficacy against a broader range of pathogens.